Cardiac Complications of Hyperthyroidism: Echocardiographic Evaluation of 69 Hyperthyroid Patients - Ansari, SM; Haider, S; Awal, MA; Khanam, N; Siddique, AB (TAJ: Journal of Teachers Association, 2009)
Echocardiography were done on 69 patients suffering from hyperthyroidism. All of them presented with palpitation and tremor. Clinical diagnosis was confirmed by radioimmunoassay of thyroid hormones. Echocardiography as well as Electrocardiography and chest radiography were done in all of them. Forty seven patients showed different types of cardiac pathology, results of which are demonstrated in details. We conclude that thorough cardiac evaluation is necessary in all hyperthyroid patients. doi: 10.3329/taj.v17i1.3481 TAJ 2004; 17(1) : 6-9